HASIL BELAJAR BERBICARA BAHASA JERMAN MELALUI PENERAPAN TEKNIK IGA (INFORMATION GAP ACTIVITIES) SISWA KELAS XI IPS-2 SMA NEGERI 3 KEDIRI - LAILATUL JAMILA, FESNIA (LATERNE, 2017)
Speaking is a process of delivering information or ideas from a speaker to a listeners. In the process of speaking, the speaker is a communicator and the listener is a communicant. Many facts show not all students are brave and willing to speak in front of the class, Because students are not skilled yet to speak due to lack of practice and the conventional learning implementation, which the teacher presents the material with a lecture and the students solve the given problem. This kind of learning models make them feel bored and unmotivated to learn speaking German in class. The problem formulation in this research is : How is the effect of IGA (Information Gap Activities) implementation towards student’s learning outcomes in Germany speaking skill of class XI IPS-2 SMA Negeri 3 Kediri? This aim of this research is to describe the results of the effect of IGA (Information Gap Activities) implementation towards student’s learning outcomes in Germany speaking skill of class XI IPS-2 SMA Negeri 3 Kediri. The object of this research were 29 students of SMA Negeri 3 Kediri class XI IPS-2. This type of research is qualitative described descriptively. This research uses observation sheet to know the IGA (Information Gap Activities) technique for german speaking skill that has been made before data retrieval. They are : 1)      Devide students in pairs, 2)      Every pairs chose secreat picture randomly, 3)      Every pairs must dig up information about images obtained by asking questions or dialogue.   The results of the research IGA (Information Gap Activities) technique implementation that has been done is students can more German speaking better. This result shows  suitable from the score of German speaking which has made. Other that, suitable for train german speaking skills more effective and it is more fun in learning Germany language. Keywords: speaking skills, teknik IGA (Information Gap Activities)